Prisoners as Patients: The Opioid Epidemic, Medication-Assisted Treatment, and the Eighth Amendment. Issue 2 (June 2018) - Linden, Michael; Marullo, Sam; Bone, Curtis; Barry, Declan T.; Bell, Kristen
This article argues that correctional institutions violate the Eighth Amendment when they refuse to establish MAT programs and prevent doctors from exercising medical judgment to properly treat incarcerated people with OUD.